2015
DOI: 10.1146/annurev-nucl-102014-022331
|View full text |Cite
|
Sign up to set email alerts
|

Parity and Time-Reversal Violation in Atomic Systems

Abstract: Studying the violation of parity and time-reversal invariance in atomic systems has proven to be a very effective means for testing the electroweak theory at low energy and searching for physics beyond it. Recent developments in both atomic theory and experimental methods have led to the ability to make extremely precise theoretical calculations and experimental measurements of these effects. Such studies are complementary to direct high-energy searches, and can be performed for just a fraction of the cost. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
90
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 214 publications
0
90
0
2
Order By: Relevance
“…Taking into account the recent atomic structure calculation [160], the experimental value of the weak charge of 133 55 Cs is given by [85] Q exp Comparing this with Eq. (5.14), we obtain the corresponding 2σ bounds on λ ed and λ ed as a function of the LQ mass as follows:…”
Section: Atomic Parity Violationmentioning
confidence: 99%
“…Taking into account the recent atomic structure calculation [160], the experimental value of the weak charge of 133 55 Cs is given by [85] Q exp Comparing this with Eq. (5.14), we obtain the corresponding 2σ bounds on λ ed and λ ed as a function of the LQ mass as follows:…”
Section: Atomic Parity Violationmentioning
confidence: 99%
“…The most promising experimental observable to probe the CP violation of new physics is the electric dipole moment (EDM) [6][7][8][9][10][11][12][13][14][15][16]. The EDM is measurable in many systems, and many experimental measurements were done so far, including the neutron [17], atoms [18][19][20][21][22], molecules [23,24], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of weak-force-induced effects in atomic systems has been the focus of experiments in the last four decades (see, for example, reviews [2][3][4]). The first experiments were motivated by the work of Bouchiat and Bouchiat [5] which showed that weak-interactioninduced observables in atoms are enhanced and therefore are detectable in systems with large atomic number.…”
Section: Introductionmentioning
confidence: 99%